The secret of the visible structures: The Parthenon, the Sainte Chapelle and two houses of Mies van der Rohe (ARQUISUR Revista, 2020)
Spiro Kostof tells in his History of Architecture, how in the eighteenth century there was a theoretical current that advocated the architecture of classical Greece as an example of a rational architecture in which the structure, the columns, behaved as they really should be, that is, functional members of the Architecture, and not decorative elements. These theorists, among whom were Carlo Lodoli or Abate Laugier, encouraged to recover this model, and also the Gothic models, as an example of an honest and essential architecture. But the truth is that when we analyze in depth archetypes of classical Greece or the Gothic, we find something that goes beyond the mere exposition of the structure and its rational use. And we find how these Architectures of visible structure, can actually be models for another type of architecture in which the structure has a rather illusory character. The objective of this article is precisely to discover this secret.
Keywords: structures, architecture of classical greece, gothic architecture, modern architecture, visual communication